Determinants of Superpower Economic Growth - Nur Rachmat Arifin; Hawa’ Hidayatul Hikmiyah; Hariyanto (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2022)
Countries in various parts of the world make economic growth the initial goal of achieving a country, one indicator used to view economic growth and one of which is the increase in Gross Domestic Product. GDP is the total value of the production of goods or services in a country for one year. This study aims to see what are the factors that influence the economic growth of the superpowers with exports, inflation, and exchange rates, and unemployment as the independent variable and GDP as the dependent variable. This research uses secondary data in the form of a combination of cross-sectional data and time series (panel data). The analytical method used is a panel data regression with a flat model model, covering six countries, namely America, China, India, Korea, Japan, and Thailand during the period 1991-2019. The results show that the Export variable, Exchange Rate, has a significant effect on GDP. Meanwhile, two independent variables, namely inflation, unemployment, did not have a significant effect on the dependent variable. Keyword: Export Superpower, Inflation, Exchange Rate, Unemployment